Desain Pengembangan Kurikulum PAI Di Sekolah Menengah Atas (SMA) - Mona Nopitasari; Desy Eka Citra Dewi (GHAITSA : Islamic Education Journal, 2024)
The aim of this study explains that the curriculum has an important role in education, including conservative, critical and creative roles. This article will discuss curriculum development design as part of learning planning in the field of education. The school curriculum must reflect the range of knowledge, skills, attitudes and values that each student who completes school is expected to have. The method used is a scientific method to obtain data for certain purposes and uses. In this research, the library research method or literature study is used as a data collection technique by reviewing literature related to the problem being solved. Where to get data from books, journals, documents and so on. The research results explain that curriculum design is a framework for compiling curriculum organization and is the preparation of one of the curriculum components, namely the content of curriculum material. Curriculum designs that can be applied in PAI curriculum development are: Subject Centered Design (SCD), Learner-Centred Design (LCD), Problem Centered Design (PCD), and Social Function Design (SFD). The development of an Islamic education curriculum is very important to create better teaching and learning conditions and meet the needs of students and society.